Implementación de una plataforma digital como herramienta para la capacitación sobre el uso de equipos biomédicos en el instituto del corazón de Bucaramanga (2020)
Within the services provided at the Instituto del corazón de Bucaramanga or ICB, several biomedical equipment are handled daily, presenting repeated questions about its principles of operation and functioning, a situation that has emphasized the need to provide training to healthcare personnel. The biomedical department, in charge of these trainings, expressed the difficulty of carrying out these training sessions due to the usual rotation and recent increase of assistance personnel that caused the implementation of an Intensive Care Unit for positive patients of COVID-19. This business practice proposed the adaptation of an open source platform as a means of training on the use of certain biomedical equipment, in order to reduce the time this activity consumed, given the flow of care personnel demanded by the institution. The final result of the platform was well received by the ICB facilities and met the initial expectations of the care staff, according to the comments received in the last phase of the project. With the record of its effectiveness, the leader of the Biomedical department postulates this platform before the institution's directors, as a requirement for the induction of any ICB care services worker.